Heat treatment method for improving strength and plasticity matching of metastable beta titanium alloy
By using two-phase zone solid solution, furnace cooling, air cooling and aging treatment heat treatment methods in metastable β titanium alloys, a heterostructure structure is formed, and the problem of insufficient plastic deformation ability of the alloy under high stress environments is solved, and excellent strong plastic matching and comprehensive performance improvement is achieved.
Patent Information
- Application Number
- CN202411881778.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Metastable β-titanium alloys have insufficient plastic deformation capabilities under high stress environments, which limits their wider application.
Through two-phase zone solid solution treatment, furnace and air-cooling treatment, and aging treatment, heterostructure structures of micron-sized striped α phase and nano-sized needle-shaped secondary α phase are formed.
It has achieved excellent strong plastic matching of metastable β-titanium alloy, improved tensile strength, yield strength, elongation of break and fracture toughness, and its comprehensive performance is significantly better than traditional methods.
Smart Images

Figure CN119615036A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal mechanical heat treatment, and in particular to a heat treatment method for improving the strength-plasticity matching of a metastable beta titanium alloy. Background Art
[0002] Titanium alloys have the characteristics of high specific strength, resistance to low and high temperatures, good fatigue resistance and corrosion resistance, and are therefore widely used in aerospace, marine and shipbuilding and other fields. Metastable β titanium alloys, as a special type of titanium alloy, are characterized by containing an appropriate amount of β-stabilizing elements (such as molybdenum, niobium, etc.), which allows the alloy to maintain a β-phase structure at room temperature. However, metastable β titanium alloys have some problems in terms of strength-plasticity matching, especially in high stress environments, where the plastic deformation capacity is insufficient, which to some extent limits their wider application.
[0003] The presence of α phase in metastable β titanium alloy has an important influence on the strength and plasticity of the material. According to the morphology and distribution characteristics of α phase, it can be divided into four categories: Widmanstatten structure, equiaxed structure, dual structure and basket structure. Widmanstatten structure shows high fracture toughness, but low fatigue performance and plasticity; the strength of dual structure is slightly lower than that of basket and dual structure, but better plasticity; the mechanical properties of dual structure are similar to those of equiaxed structure, and the fracture toughness is slightly higher; the comprehensive performance of basket structure is between equiaxed structure and Widmanstatten structure, with excellent fracture toughness and endurance strength, and plasticity is lower than that of equiaxed and dual structure, but higher than that of Widmanstatten structure. Traditional metastable β titanium alloy has certain limitations in strength and plasticity matching, especially in high stress environment, its plastic deformation ability often cannot meet the needs of practical applications. The development of high-performance titanium alloys with high strength, high plasticity and high fracture toughness is conducive to ensuring the safe service of titanium alloy structural parts and further expanding the application of titanium alloys.
[0004] At present, the heat treatment methods for metastable β titanium alloys mainly include solution treatment, single-stage aging, double-stage aging and double annealing. Solution treatment is to heat the alloy to the β phase region or the α+β two-phase region for solution treatment to prepare the structure for the subsequent aging treatment. Aging treatment is to keep the alloy at an intermediate temperature for a period of time after solution treatment to promote the precipitation of the secondary α phase, thereby improving the strength of the material. However, the strength difference between the hard secondary α phase and the soft β phase often causes strain incompatibility, which makes it easy to generate stress concentration at the interface of the two phases, causing holes or even microcracks, resulting in insufficient plasticity of the alloy. Therefore, in the heat treatment process of metastable β titanium alloy, how to effectively control the ratio and morphology of the α phase and β phase to obtain a better match between strength and plasticity has always been the focus and difficulty of research. Summary of the invention
[0005] The present invention aims to provide a heat treatment method for improving the strength-plasticity matching of a metastable β titanium alloy, and achieves excellent matching of strength, plasticity and fracture toughness of the metastable β titanium alloy by optimizing heat treatment process parameters.
[0006] In a first aspect, the present invention provides a heat treatment method for improving the strength-ductility matching of a metastable β titanium alloy, comprising the following steps:
[0007] Step 1: Two-phase solution treatment
[0008] The metastable β titanium alloy with basket structure is placed in a heat treatment furnace and subjected to solution treatment and heat preservation at a two-phase region temperature for 0.5 to 1.5 hours;
[0009] Step 2: Furnace cooling and air cooling
[0010] The solution treated alloy is directly furnace cooled to 500℃~650℃, and then air cooled out of the furnace;
[0011] Step 3: Aging treatment
[0012] The alloy after solution treatment, furnace cooling and air cooling is placed in a heat treatment furnace at a certain temperature for aging and heat preservation for 4 to 8 hours, and then taken out of the furnace for air cooling.
[0013] Furthermore, in step 1, the temperature is kept at 25°C to 50°C, which is lower than the β phase transformation point, for 0.5 to 1.5 hours. The main purpose of the two-phase region solution treatment is to dissolve most of the α phase into the β phase, and only retain a certain proportion of the strip α phase.
[0014] Furthermore, in step 1, the solution temperature is 815° C. and the insulation time is 1 hour.
[0015] Furthermore, in step 2, the furnace is cooled to 550° C. to 650° C., and then air-cooled. The furnace cooling and air-cooling treatments can coarsen and grow the residual strip-shaped α phase, thereby improving the plastic deformation capacity of the primary strip-shaped α phase.
[0016] Furthermore, in step 3, aging treatment is performed at 500°C to 650°C, preferably 550°C, for 8 hours. Aging treatment can promote the further precipitation of fine dispersed secondary α phase in the residual metastable β phase, thereby improving the strength of the material.
[0017] Furthermore, the molybdenum equivalent (Mo) of the metastable β titanium alloy with basket structure is [eq] ) is between 10 and 20.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention forms a certain proportion of micron-sized strip α phase through two-phase solid solution, furnace cooling + air cooling treatment, and precipitates nano-sized needle-shaped secondary α phase in the residual β through aging treatment, and finally obtains a heterogeneous structure in which the micron-sized strip α phase surrounds the nano-sized needle-shaped secondary α phase and the residual β phase.
[0020] (2) The present invention improves the deformation capacity of the α phase by forming a coarsened strip-shaped α phase through two-phase solid solution, furnace cooling + air cooling treatment, and improves the strength of the alloy by precipitating a fine secondary α phase through aging treatment, ultimately enabling the alloy to have excellent strength-plasticity matching.
[0021] (3) The present invention achieves a tensile strength of 984-1034 MPa, a yield strength of 916-953 MPa, an elongation at break of 18.9%-20.8%, and a fracture toughness of 110-121 MPa·m by finely controlling the ratio, morphology, and size of the α phase. 0.5 , with excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention is described in detail below with reference to the accompanying drawings.
[0023] Figure 1 The titanium alloy microstructures of different multiples in Example 1 were obtained by solution treatment at 815°C for 1 hour, furnace cooling to 650°C, air cooling, and then heat preservation at 550°C for 8 hours and air cooling.
[0024] Figure 2 The microstructure diagrams of titanium alloys of different multiples are shown in Example 2 after being solution-solution-treated at 815°C for 1 hour, furnace-cooled to 600°C, taken out for air cooling, and then kept at 550°C for 8 hours, and then taken out for air cooling.
[0025] Figure 3 In Example 3, the titanium alloy microstructures of different multiples were obtained by solution treatment at 815°C for 1 hour, furnace cooling to 550°C, air cooling, and then heat preservation at 550°C for 8 hours.
[0026] Figure 4 The microstructure diagrams of titanium alloys with different multiples of air cooling are shown in Example 1 after solution treatment at 815°C for 1 hour, furnace cooling to 700°C, and then taking out for air cooling, and then keeping at 550°C for 8 hours.
[0027] Figure 5 The microstructure diagrams of titanium alloys with different multiples are shown in Example 2, which were solution-treated at 870°C for 1 hour, furnace-cooled to 550°C, taken out for air cooling, and then kept at 550°C for 8 hours, and then taken out for air cooling.
[0028] Figure 6 These are the microstructure diagrams of titanium alloys of different magnifications in Example 3 that were solution-treated at 815°C for 1 hour and then air-cooled.
[0029] Figure 7 The microstructure diagrams of titanium alloys of different magnifications in Example 4 are obtained by solution treatment at 815°C for 1 hour, air cooling, and then heat preservation at 550°C for 8 hours and air cooling.
[0030] Figure 8 It is a tensile stress-strain curve diagram of the titanium alloy in Examples 1 to 3 and Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0032] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0034] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0035] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.
[0036] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.
[0037] The present invention uses a metastable β titanium alloy forging blank with a basket structure for heat treatment. The basket structure is one of the four common types of structures in titanium alloys, and can be obtained by β forging, quasi-β forging and other processes disclosed in existing literature. The alloy used in the implementation case of the present invention is Ti-4Al-6Mo-3Nb-2Cr-1Zr-1Sn (β phase transition point is 845°C), and the molybdenum equivalent is 11.6, but the heat treatment method proposed in the present invention is not limited to this alloy.
[0038] Example 1
[0039] This embodiment includes the following steps:
[0040] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 815°C for 1 hour.
[0041] Step 2: directly furnace cool the alloy obtained in step 1 to 650°C, and then air cool it out of the furnace.
[0042] Step 3: The alloy obtained in step 2 is kept at 550°C for 8 hours, and then removed from the furnace and air-cooled.
[0043] Figure 1 This is the SEM microstructure of the alloy after heat treatment in this embodiment. It can be seen that the interior of the β grain contains coarse micron-sized strip-shaped α phase and fine nano-sized needle-shaped secondary α phase. The large-sized α phase surrounds the fine secondary α phase to form a heterogeneous structure.
[0044] Example 2
[0045] This embodiment includes the following steps:
[0046] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 815°C for 1 hour.
[0047] Step 2: directly furnace cool the alloy obtained in step 1 to 600°C, and then air cool it out of the furnace.
[0048] Step 3: The alloy obtained in step 2 is kept at 550°C for 8 hours, and then removed from the furnace and air-cooled.
[0049] Figure 2 This is the SEM microstructure of the alloy after heat treatment in this example. It can be seen that the β grains contain coarse micron-sized strip-shaped α phase and fine nano-sized needle-shaped secondary α phase. The large-sized α phase surrounds the fine secondary α phase to form a heterogeneous structure.
[0050] Example 3
[0051] This embodiment includes the following steps:
[0052] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 815°C for 1 hour.
[0053] Step 2: directly furnace cool the alloy obtained in step 1 to 550° C., and then air cool it out of the furnace.
[0054] Step 3: The alloy obtained in step 2 is kept at 550°C for 8 hours, and then removed from the furnace and air-cooled.
[0055] Figure 3This is the SEM microstructure of the alloy after heat treatment in this example. It can be seen that the β grains contain coarse micron-sized strip-shaped α phase and fine nano-sized needle-shaped secondary α phase. The large-sized α phase surrounds the fine secondary α phase to form a heterogeneous structure.
[0056] Comparative Example 1
[0057] This comparative example comprises the following steps:
[0058] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 815°C for 1 hour.
[0059] Step 2: directly furnace cool the alloy obtained in step 1 to 700°C, and then air cool it out of the furnace.
[0060] Step 3: The alloy obtained in step 2 is kept at 550°C for 8 hours, and then removed from the furnace and air-cooled.
[0061] Figure 4 This is the SEM microstructure of the alloy after heat treatment in this comparative example. It can be seen that the β grains contain more secondary α phases, which greatly hinder the dislocation slip, making the alloy plasticity significantly lower than that of Examples 1 to 3.
[0062] Comparative Example 2
[0063] This comparative example comprises the following steps:
[0064] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 870°C, i.e., 25°C higher than the β phase transformation point, for 1 hour.
[0065] Step 2: directly furnace cool the alloy obtained in step 1 to 550° C., and then air cool it out of the furnace.
[0066] Step 3: The alloy obtained in step 2 is kept at 550°C for 8 hours, and then removed from the furnace and air-cooled.
[0067] Figure 5 This is the SEM microstructure of the alloy after heat treatment in this comparative example. Due to the solid solution in the β phase region, furnace cooling causes a large amount of lath α phase to precipitate, crisscross, and parallel α clusters appear, which is not conducive to the strength and plasticity matching of the alloy.
[0068] Comparative Example 3
[0069] This comparative example comprises the following steps:
[0070] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 815°C for 1 hour.
[0071] Step 2: Take the alloy obtained in step 1 out of the furnace and air cool it directly.
[0072] Figure 6 3 is the SEM microstructure of the alloy after heat treatment in this comparative example. It can be seen that the interior of the β grain contains only a small amount of strip-shaped α phase.
[0073] Comparative Example 4
[0074] This comparative example comprises the following steps:
[0075] Step 1: Place the basket structure metastable β titanium alloy material in a heat treatment furnace and keep it at 815°C for 1 hour.
[0076] Step 2: Take the alloy obtained in step 1 out of the furnace and air cool it directly.
[0077] Step 3: The alloy obtained in step 2 is kept at 550°C for 8 hours, and then removed from the furnace and air-cooled.
[0078] Figure 7 This is the SEM microstructure of the alloy after heat treatment in this comparative example. It can be seen that a large amount of dispersed α phase precipitates from the β grains, presenting a typical basketweave structure with high strength but obviously insufficient plasticity.
[0079] Performance comparison
[0080] The titanium alloys in Examples 1 to 3 of the present invention present heterogeneous structural organizations and exhibit excellent strength-ductility matching. The specific performance parameters are as follows:
[0081] The tensile strength (UTS) is 984-1034MPa, the yield strength (YS) is 916-953MPa, the elongation at break (EL) is 18.9%-20.8%, and the fracture toughness (K IC ) is 110~121MPa·m 0.5 The comprehensive performance is significantly better than that of comparative examples 1 to 4. The main performance comparison test results are shown in Tables 1 and Figure 8 .
[0082] Table 1: Performance comparison of the heat treatment method of the present invention and other heat treatment methods
[0083]
[0084] Figure 8 3 is a tensile curve diagram of the embodiments of the present invention and the comparative example. It can be seen that the strength of the alloy cooled to 700°C in the two-phase zone and aged is acceptable, but the plasticity and fracture toughness are average; the strength-plasticity matching of the alloy cooled to 550°C in the β single-phase zone and aged is not very high; only the strength of the solid solution sample is low and the plasticity is average; the strength of the solid solution + aging sample is improved, but the plasticity and fracture toughness are reduced at the same time. Embodiments 1 to 3 of the present invention have high strength, high plasticity and high fracture toughness, overcoming the bottleneck of strength-plasticity matching of the alloy.
Claims
1. A heat treatment method for improving the strength-plasticity matching of metastable β titanium alloy, characterized in that: The following steps are involved: Step 1: Two-phase solution treatment The metastable β titanium alloy with basket structure is placed in a heat treatment furnace and solution-treated at a two-phase temperature for 0.5 to 1.5 hours; Step 2: Furnace cooling and air cooling The solution treated alloy is directly furnace cooled to 500℃ ~ 650℃, and then air cooled out of the furnace; Step 3: Aging treatment The alloy after solution treatment, furnace cooling and air cooling is placed in a heat treatment furnace at a certain temperature for aging and heat preservation for 4 to 8 hours, and then taken out of the furnace for air cooling.
2. The method according to claim 1, characterized in that Solution heat preservation is carried out at a temperature of 25℃ to 50℃ below the β transformation point for 0.5 to 1.5 hours.
3. The method according to claim 1, characterized in that The solution temperature is 815°C and the holding time is 1 hour.
4. The method according to claim 1, characterized in that In step 2, the furnace is cooled to 550°C ~ 650°C and then air-cooled.
5. The method according to claim 1, characterized in that In step 3, aging treatment is performed at 500°C to 650°C, preferably 550°C, for 8 hours.
6. The method according to claim 1, characterized in that The molybdenum equivalent of the metastable β titanium alloy with basketweave structure is between 10 and 20.
Citation Information
Patent Citations
High-strength metastable beta-type titanium alloy bar and production method thereof
CN104726746A
Method for improving fracture toughness of two-phase region of TC4-DT titanium alloy bar material
CN109161829A
Heat treatment process of titanium alloy
CN110273118A
Heat treatment method for improving plasticity and toughness of metastable beta titanium alloy
CN116162879A
High-strength and high-toughness Ti-5321 alloy and heat treatment method thereof
CN118086807A